Ekspektasi Masyarakat Bekasi terhadap Keberadaan Bank Syari’ah, Potensi dan Pengembangan - Isfandayani . (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2011)
This study aimed to assess public expectations regarding the existence of Islamic banks of Bekasi, Potential and Development. From this study it can be concluded that the performance of Islamic banking is good, but still below the conventional market, especially in terms of cultivation. Achievement of the Islamic banking market is only 3%, so it needs to be improved in its marketing. It should be underlined that the information until the consumer is still limited so it will affect the decision process. The potential economic and population Bekasi City and can be targeted in the expansion area and the achievement of the target funding, financing, and services. Public knowledge about the Islamic banks is adequate, but less depth, so it needs socialization. The need for proper publicity is one important way to socialize. Bekasi community expectations that represented the respondents in this study is the addition of the service area of both branches and ATM outlets, a branch of Islamic banks in the traditional markets are great because this is where the real sector grew rapidly evolving andallegedly moneylenders. Another expectation is that there is excellent service with speed, accuracy, and friendliness giving rise to a sense of comfort and safety when working with Islamic banks. Easy financing micro-scale, increased sharing of savings is expected. Surely Islamic banks must be prepared to fund managers that are reliable and understand the rules of sharia